The acute effects of post-activation potentiation on shot put performance in female throwers - Kontou, E.; Berberidou, F.; Mantzouranis, N.; Piliandis, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Limited research is available on the subsequent effects of the upper-body post-activation potentiation (PAP) on the competitive throwing activity in trained experts (Terzis et al., 2009). Therefore, the aim of this study was to evaluate the precise responses of two upper-body PAP protocols on the shot put performance in experienced female throwers. Methods: Ten (n=10) female collegiate throwers aged 18.9±1.2yrs participated in this study. In the initial screening, the throwers` personal best in Shot Put event was recorded and the 1RM in bench press lift was tested. The throwers performed in competitive conditions, in counterbalanced order in 2 testing trials with a 48-hour interval: 1st = 3 throws with a 10min rest (noPAP1) & 4 plyometric push-ups prior to the 3 throws (PAP1) and 2nd = 3 throws with a 10min rest (noPAP2) & 6s isometric push-ups prior to the 3 throws (PAP2). Their performance was carried out from the final release position with regulation weight implement. The Wilcoxon test and the Spearman`s rho correlation were applied for the continuous data analysis. Results: The statistical procedures revealed that the female throwers improved their performance by applying both PAP protocols: noPAP1=8.03m vs PAP1=8.15m, (p=0.31) & noPAP2=7.99m vs PAP2=8.13m, (p=0.50). In addition, the Spearman`s analysis showed that the performance which was recorded by using the PAP1 was highly correlated with the throwers` personal best in shot put (0.76, p<0.05) but not with their bench press lift, (0.37, p=0.30). Similarly, the PAP2 protocol indicated high correlation with the female throwers` personal best in shot put (0.75, p<0.05) while no correlation was observed between the 6s isometric push-ups and their bench press lift, (0.49, p=0.16). Discussion: The major finding of this study was that the plyometric push-ups seem to be more beneficial than the isometric pushups or the no-treatment in the female shot put throwers. Thus, in conjunction with relevant bibliography (Bellar & Judge, 2011), this study confirms that the plyometric exercise highly influences the ballistic throwing performance. Furthermore, the direct correlation between both PAP protocols and the female throwers` personal best in shot put proves that, the higher the training level, the greater the effect of their upper-body PAP treatment. Conclusively, the present study confirms that the post-activation potentiation by applying the plyometric push-ups affects positively the competitive performance of expert female throwers.